Potential Application of Green Composites for Cross Arm Component in Transmission Tower: A Brief Review - M. R. M. Asyraf; M. R. Ishak; S. M. Sapuan; N. Yidris; R. A. Ilyas; M. Rafidah; M. R. Razman (International Journal of Polymer Science)
Recently, advanced technologies exploit materials from nonrenewable resources such as petroleum, natural gas, metal ores, and minerals. Since the depletion of these resources and environmental issues, it has brought attention to researchers to progress in the development of biodegradable materials from green composites. Most biofibres and biopolymers are obtained from agricultural waste products either from stem, leaf, stalk, or fruit. Nowadays, green composites with well-regulated life span have been widely discussed in numerous fields and applications. Some studies have shown that biofibres and biopolymers have comparable mechanical, thermal, and physical properties with glass fibre and other synthetic polymers. Thus, researchers are progressively narrowing down the development of green composite materials in many high strength applications, such as house deck and automotive components. This review focuses on the background of green composites (natural fibres and biopolymers), the manufacturing processes, potential applications in cross arm structures, and testing evaluations. This article also focuses on the specific current cross arm configurations and the pultrusion process to form squared hollow section beams. Many open issues and ideas for potential applications of green composites are analysed, and further emphases are given on the development of environmentally friendly material structures. Hence, the article is expected to deliver a state-of-art review on manufacturability and perspectives of natural fibre reinforced biopolymer composite cross arms for transmission towers.